Compensation Effect on Cu-Co-Fe Oxide Catalysts of CO Oxidation - O. Byeda; E. Ischenko; V. Yatsimirsk (Хімія, фізика та технологія поверхні)
The occurrence of compensation effect on massive and supported oxide catalysts of CO oxidation is shown. The explanation of compensation effect is offered based on the data on the surface state of the catalysts that are obtained by means of thermally programmed desorption method with mass spectrometric registration of the desorbed particles (TPD MS).